RESPONSIVENESS SISI KESEHATAN DALAM MEMBERIKAN PELAYANAN KESEHATAN - Wa Ode Siti Orianti; Mubasysyir Hasanbasri; Adi Utarini (Journal of Health Service Management, 2020)
Background: Responsiveness according to WHO is the result that can be achieved when an institution designed so that they areaware of and respond appropriately to the expectations of a legitimate, based on measurements through eight domains are: dignity,attention immediately, autonomy, choice of health care providers, clear communication, confidentiality, quality of basic amenities, andaccess to social support networks.Objective: To analyze the responsiveness of the hospitals and health centers in providing health services.Methods: A descriptive study with qualitative methods. This research uses descriptive type so that the researcher will analyze howresponsiveness in terms of health in providing health services to the community. This research was conducted in Buru Regency with 22 respondents.Results: The experience of respondents to the responsiveness in hospitals that view based on variable dignity officers have notprovided services to the fullest and less maintain patient privacy. Variable attention in hospitals and health center patients are stillwaiting long in getting service especially in emergency situations because the doctor was not in place. The variable access to thenetwork for the distance from home to health facilities is still very far away and unreached by the public outside the city as well as a drugthat is not yet complete. The variable quality of amenities in hospitals on quality very bad environment that makes the patient feelnot comfortable and safe. Variable trust in hospitals and community health centers are still not so sure about health care because theybelieve in the healing traditions.Conclusion: Responsiveness of the health in Hospitals Buru and Air Buaya Health Centers not responsive that in view based on variablesdignity, attention, access to the network, quality of amenities and trust.